The Need for Affirming Health Care among LGBTQ+ Survivors of Intimate Partner Violence (Global Journal of Human-Social Science, 2024)
Lesbian, gay, bisexual, trans, queer, and others who are not heterosexual and cisgender (LGBTQ+) are a growing population in the United States and globally; however, they are more likely to report health conditions while are simultaneously more likely to struggle attaining patient centered or affirming health care. Struggles to receive care are amplified by the lack of formal policy that views health care as a human right. This population is also more vulnerable to several risk factors, including intimate partner violence (IPV) than cisgender and heterosexual people. Therefore, they are more likely to necessitate medical care due to injuries (e.g., broken bones, vaginal trauma, lost teeth). In the absence of macro-level policy protections, we make the case for patient-centered and affirming health care that addresses health inequities and the negative health outcomes for IPV survivors. We provide recommendations for providers in primary care, emergency rooms, obstetrics and gynecology, and dentistry.
Keywords: abuse; bisexual; constitutional rights; domestic violence; fourteenth amendment; gay; lesbian; medicine; sexual minority; transgender